APLIKASI PENGENALAN AKSARA BATAK BERBASIS ANDROID MENGGUNAKAN API GESTURE - Hotma Pangaribuan (UNIVERSITAS PELITA HARAPAN, 2017)
The script of the archipelago is a script used specifically to write a particular regional language. Dijawa known as Javanese script, is known as Balinese script, and in Batak known as Batak script. This research aims to introduce Batak script especially Toba Batak script based on android using Aplication programming interface (API) with Gesture model. The focus of this research is how to translate Indonesian letters, words and sentences into Toba Batak script on smartphone devices and the like that can be used by users by downloading the application on the playstore. From the results of this study can be introduced type of type of letters or script Batak, for the preservation of Toba Batak script maintained. While the method used to design the application of Batak Toba script is UML (Unified Modeling Language) is the most frequently used methodology today for the analysis and design of the system with object oriented methodology that adapt to the rampant use of object oriented programming language